Composite positive electrode material, preparation method thereof, positive electrode plate, secondary battery and electric device

By preparing polyanionic positive electrode materials in one-step method and forming a graphene cladding layer, the problems of complex and high cost of the preparation process of graphene composite positive electrode materials in the prior art are solved, and high energy density and electrochemical performance are improved.

CN119833582APending Publication Date: 2025-04-15CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202410021028.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-05
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art has complex processes and high costs when preparing graphene composite cathode materials, resulting in a degradation of the electrochemical properties of the materials.

Method used

A polyanionic positive electrode material is prepared by a one-step method, and a carbon material containing graphene is formed at the same time. The carbon material is coated on the surface of the positive electrode material or dispersed between its particles, simplifying the process flow and controlling the sintering temperature in the range of 750°C-840°C.

Benefits of technology

The high powder compaction density of composite positive electrode materials is achieved, and the energy density and electrochemical performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833582A_ABST
    Figure CN119833582A_ABST
Patent Text Reader

Abstract

The invention provides a composite positive electrode material, a preparation method thereof, a positive electrode plate, a secondary battery and an electric device. The preparation method comprises the following steps: mixing a lithium source, a phosphorus source, an iron source, a carbon source and a carbon graphitization catalyst with a solvent according to a preset proportion to form mixed slurry; grinding and drying the mixed slurry to obtain a mixed dry substance; and sintering the mixed dry substance at the temperature of 750-840 DEG C to obtain the composite positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a composite positive electrode material, a preparation method thereof, a positive electrode sheet, a secondary battery and an electrical device. Background Art

[0002] Graphene is a two-dimensional material composed of carbon atoms arranged periodically in a hexagonal lattice with sp2 hybrid bonds. Theoretically, graphene is only one carbon atom thick and has excellent physical properties such as large theoretical specific surface area, high electron mobility, high thermal conductivity, and high Young's modulus, thus showing potential application value in many fields such as mechanics, energy storage, catalysis, electronic devices, and environmental treatment. It should be noted that the two-dimensional carbon graphene structure prepared by actual synthesis is generally composed of multiple layers of carbon atoms.

[0003] Compared with traditional conductive agents in lithium-ion batteries, graphene has better conductivity and ultra-fast two-dimensional planar transfer characteristics, as well as very small packing density. That is, it is possible to achieve the effect of a large amount of traditional conductive agents by adding a very small amount of graphene, thereby reducing the proportion of conductive agents and increasing the proportion of electrode materials and the energy density of devices.

[0004] Polyanion cathode materials, including phosphate cathode materials, have poor electronic and ionic conductivity due to their structural characteristics, and require the use of highly conductive coatings and nano-scale methods to improve their electrical properties. Graphene composite cathode materials are a very effective modification method, and the electrochemical properties of composite materials can be significantly improved.

[0005] Since the preparation of graphene needs to be carried out at high temperature, and when the positive electrode material is calcined at high temperature, the particle size of the positive electrode material will grow significantly and the impurity phase will be generated, resulting in a decrease in the electrochemical performance of the material. Therefore, the conventional method for preparing graphene composite positive electrode materials is to first prepare graphene materials, then mix the graphene materials and the positive electrode material precursors and sinter them. Therefore, the process is complicated and the cost is high. Summary of the invention

[0006] The present application provides a composite positive electrode material, a preparation method thereof, a positive electrode plate, a secondary battery and an electric device, so as to simplify the preparation process of the composite positive electrode material and reduce its cost.

[0007] The first aspect of the present application provides a method for preparing a composite positive electrode material, which comprises: mixing a lithium source, a phosphorus source, an iron source, a carbon source, and a carbon graphitization catalyst with a solvent in a predetermined proportion to form a mixed slurry; grinding and drying the mixed slurry to obtain a mixed dry matter; sintering the mixed dry matter to obtain a composite positive electrode material, and the sintering temperature is 750°C-840°C.

[0008] The preparation method of the composite positive electrode material of the first embodiment of the present application adopts a one-step method to prepare a polyanionic positive electrode material while forming a carbon material containing graphene. The carbon material is coated on at least part of the surface of the polyanionic positive electrode material to form a coating layer, and / or is dispersed between the particles of the polyanionic positive electrode material. The graphene is connected to the coating layer or is freely distributed between the particles of the polyanionic positive electrode material, which simplifies the preparation process of the composite positive electrode material. In addition, the present application further controls the sintering temperature within the range of 750°C-840°C, so that large-size particles and small-size particles are formed in the formed composite positive electrode material, and the grading of large and small particles is achieved, so that the obtained composite positive electrode material has a higher powder compaction density, for example, the powder compaction density of the composite positive electrode material at 226.0738Mpa (corresponding to 3T) is ≥2.42g / cm 3 .

[0009] In any embodiment of the first aspect of the present application, the carbon graphitization catalyst includes any one or more of metals or metal oxides, the metal includes Fe and / or Ni, and the metal oxide includes any one or more of FeO, Fe3O4, Fe2O3, CuO, NiO, MnO, Mn3O4, V2O5, V2O3 or VO4. As catalysts, the above metals and metal oxides are relatively stable during the sintering process and are not easily burned away.

[0010] In any embodiment of the first aspect of the present application, the average particle size of the carbon graphitization catalyst is 100nm-400nm, and can be 100nm-330nm. When the nano-scale carbon graphitization catalyst within the above particle size range is mixed with other materials, a higher contact area with the carbon source can be obtained as much as possible, thereby improving the catalytic efficiency.

[0011] In any embodiment of the first aspect of the present application, the mass ratio of the carbon graphitization catalyst to the carbon source is 1:100-1:30.

[0012] In any embodiment of the first aspect of the present application, the mixed slurry also includes lithium-doping element raw materials, phosphorus-doping element raw materials, iron-doping element raw materials, and oxygen-doping element raw materials. In the mixed slurry, the total molar number of lithium element in the lithium source and the doping element in the lithium-doping element raw materials is M1, the total molar number of iron element in the iron source and the doping element in the iron-doping element raw materials is M2, the total molar number of phosphorus element in the phosphorus source and the doping element in the phosphorus-doping element raw materials is M3, M1:M2:M3 is (1.0-1.1):(0.95-1.0):(1.0-1.1), and M2:M3 is less than 1:1, and the ratio of the mass of the carbon graphitization catalyst to the total mass of the iron source and the iron-doping element raw materials is (1:1000)-(1:100).

[0013] In any embodiment of the first aspect of the present application, M2:M3 is greater than or equal to 0.96:1 and less than 1:1.

[0014] In any embodiment of the first aspect of the present application, the polyanionic positive electrode material includes a lithium-containing phosphate, and the lithium-containing phosphate includes at least one of lithium iron phosphate and a doped and / or coated modified compound thereof.

[0015] In any embodiment of the first aspect of the present application, the carbon source includes one or more of glucose, sucrose, fructose, citric acid, starch, polyvinyl alcohol, polyethylene glycol or polyaniline.

[0016] In any embodiment of the first aspect of the present application, grinding includes ball milling and sand milling performed sequentially; the Dv50 of the insoluble particles in the mixed slurry after ball milling is 2.0μm-5.0μm, and can be optionally 2.0μm-4.0μm; the Dv50 of the insoluble particles in the mixed slurry after sand milling is 0.3μm-1.2μm, and can be optionally 0.3μm-0.4μm.

[0017] In any embodiment of the first aspect of the present application, the process of sintering the mixed dry matter includes: heating the mixed dry matter to 780°C-820°C for 2h-9h, and keeping the temperature at 780°C-820°C for 6h-20h.

[0018] In any embodiment of the first aspect of the present application, sintering is carried out in a reducing atmosphere, the reducing atmosphere includes a reducing gas and a protective gas, optionally the reducing gas includes any one or more of hydrogen, acetone, propylene, carbon monoxide, methanol, acetylene, methane, ethylene, and ethane; optionally the protective gas includes any one or more of nitrogen and an inert gas.

[0019] In any embodiment of the first aspect of the present application, the volume content of the reducing gas in the reducing atmosphere is 1%-8%. The addition of the reducing atmosphere is not only conducive to improving the carbonization rate of the carbon source, but also has a significant improvement effect on the catalytic effect of the carbon graphitization catalyst in the form of metal oxides, further optimizing the carbon graphitization effect, so that the carbon coating layer contains more graphene content.

[0020] In any embodiment of the first aspect of the present application, after sintering, the preparation method further comprises a process of crushing the composite positive electrode material, and the Dv50 of the crushed composite positive electrode material is 0.6 μm-2.0 μm.

[0021] The second aspect of the present application provides a composite positive electrode material as described above, the composite positive electrode material comprising a polyanionic positive electrode material and a carbon material, the carbon material being coated on at least part of the surface of the polyanionic positive electrode material and / or being dispersed between the polyanionic positive electrode material particles, the carbon material comprising graphene, and the powder compaction density of the composite positive electrode material at 226.0738 Mpa is ≥2.42 g / cm 3 , optionally ≥2.53g / cm 3 .

[0022] In any embodiment of the second aspect of the present application, the room temperature turbidity of the slurry formed by mixing the composite positive electrode material and water in a mass ratio of 1:40 is 200FTU-400FTU, and can be optionally 240FTU-280FTU.

[0023] In any embodiment of the second aspect of the present application, the mass content of the magnetic substance in the composite positive electrode material is ≤1 ppm, thereby controlling the self-discharge defect of the composite positive electrode material.

[0024] A third aspect of the present application provides a positive electrode plate, comprising a positive electrode film layer, the positive electrode film layer comprising a positive electrode active material, wherein the positive electrode active material comprises the composite positive electrode material provided in any embodiment of the second aspect.

[0025] In any embodiment of the third aspect, based on the total cross-sectional area of ​​the positive electrode active material, the cross-sectional area of ​​the composite positive electrode material with a primary average particle size of 50nm-150nm accounts for 10% to 35%; the cross-sectional area of ​​the composite positive electrode material with a primary average particle size of 150nm-1500nm accounts for 30% to 60%; the cross-sectional area of ​​the composite positive electrode material with a primary average particle size of not less than 1500nm accounts for 10-35%.

[0026] A fourth aspect of the present application provides a secondary battery, comprising a positive electrode plate, wherein the positive electrode plate comprises the positive electrode plate provided in any embodiment of the third aspect.

[0027] A fifth aspect of the present application provides an electrical device, including a secondary battery, wherein the secondary battery includes the secondary battery provided in any embodiment of the fourth aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0029] Figure 1This is a transmission electron microscope (TEM) image of the composite lithium iron phosphate positive electrode material obtained in Preparation Example 1 of this application.

[0030] Figure 2 This is a transmission electron microscope image of the composite lithium iron phosphate positive electrode material obtained in comparative preparation example 1 of this application.

[0031] Figure 3 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0032] Figure 4 yes Figure 3 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0033] Figure 5 is a schematic diagram of a battery module according to an embodiment of the present application.

[0034] Figure 6 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0035] Figure 7 yes Figure 6 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0036] Figure 8 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0037] In the drawings, the drawings are not drawn to scale.

[0038] Description of reference numerals:

[0039] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0040] The following detailed description and drawings of the embodiments of the present application are used to illustrate the principles of the present application, but cannot be used to limit the scope of the present application, that is, the present application is not limited to the described embodiments.

[0041] Below, the embodiments of the composite positive electrode material, its preparation method, positive electrode sheet, secondary battery and electric device of the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0042] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0043] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0044] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0045] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0046] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or comprised.

[0047] If not otherwise specified, in this application, the term "or" is inclusive. For example, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0048] [Secondary battery]

[0049] Secondary batteries, also known as rechargeable batteries or storage batteries, refer to batteries that can continue to be used by recharging the active materials after the battery is discharged.

[0050] Normally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the battery charging and discharging process, active ions (such as lithium ions or sodium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The electrolyte is between the positive electrode sheet and the negative electrode sheet, mainly to conduct active ions.

[0051] As mentioned above, the current preparation of composite positive electrode materials requires the separate preparation of graphene, but the process is complicated and the cost is high. In order to solve this problem, in the first embodiment of the present application, a method for preparing a composite positive electrode material is provided, and the preparation method includes:

[0052] A lithium source, a phosphorus source, an iron source, a carbon source, and a carbon graphitization catalyst are mixed with a solvent in a predetermined ratio to form a mixed slurry; the mixed slurry is ground and dried to obtain a mixed dry matter; the mixed dry matter is sintered to obtain a composite positive electrode material, and the sintering temperature is 750°C-840°C.

[0053] The carbon graphitization catalyst is a catalyst that catalyzes the conversion of carbon into graphene. The composite cathode material obtained by the above preparation method includes a polyanionic cathode material and a carbon material, the carbon material is coated on at least part of the surface of the polyanionic cathode material and / or is dispersed between the polyanionic cathode material particles, and the carbon material includes graphene.

[0054] The preparation method of the composite positive electrode material of the first embodiment of the present application adopts a one-step method to prepare a polyanionic positive electrode material while forming a carbon material containing graphene. The carbon material is coated on at least part of the surface of the polyanionic positive electrode material to form a coating layer, and / or is dispersed between the particles of the polyanionic positive electrode material. It can be seen that the graphene is connected to the coating layer or is freely distributed between the particles of the polyanionic positive electrode material, thereby simplifying the preparation process of the composite positive electrode material. The present application further controls the sintering temperature within the range of 750°C-840°C, so that large-size particles and small-size particles are formed in the formed composite positive electrode material, and the grading of large and small particles is achieved, so that the obtained composite positive electrode material has a higher powder compaction density, thereby improving the energy density of the battery cell, for example, the powder compaction density of the composite positive electrode material at 226.0738Mpa is ≥2.42g / cm 3 .

[0055] As the sintering temperature increases, the particles of the composite positive electrode material grow, while the amount of graphene generated decreases. The preparation method of the present application controls the sintering temperature within the above range, thereby achieving the purpose of simultaneously improving the powder compaction density and the amount of graphene generated as much as possible, thereby improving the overall performance of the battery.

[0056] The carbon graphitization catalyst used in the present application can be selected from conventional carbon graphitization catalysts. In some embodiments, the carbon graphitization catalyst includes any one or more of metals or metal oxides, the metal includes Fe and / or Ni, and the metal oxide includes any one or more of FeO, Fe3O4, Fe2O3, CuO, NiO, MnO, Mn3O4, V2O5, V2O3 or VO4. As catalysts, the above metals and metal oxides are relatively stable during the sintering process and are not easily burned away. If metal residues appear during the metal-catalyzed carbon graphitization process, the self-discharge K value of the battery will be affected; preferably, the residues of the above metal oxides have no effect on the self-discharge K value of the battery.

[0057] In some embodiments, the carbon source dosage can be set based on the carbonization rate of different carbon sources, with the carbon formed after carbonization accounting for 0.6%-2.5% of the weight content of the composite positive electrode material as a reference. The carbonization rates of the above-mentioned different carbon sources can be obtained through experience in the field and will not be repeated in this application.

[0058] In some embodiments, the carbon source includes one or more of glucose, sucrose, fructose, citric acid, starch, polyvinyl alcohol, polyethylene glycol, or polyaniline, wherein glucose, sucrose, fructose, and citric acid are small molecule carbon sources, and starch, polyvinyl alcohol, polyethylene glycol, and polyaniline are high molecule carbon sources.

[0059] Since the one-step method of the present application uses a large variety of raw materials, the carbon source accounts for a relatively small proportion of the entire slurry, and the carbon graphitization catalyst as a catalyst accounts for an even smaller proportion in the mixed slurry. In order to further improve the catalytic effect of the carbon graphitization catalyst on the carbon source, in some embodiments, the average particle size of the carbon graphitization catalyst is 100nm-400nm, which can be optionally 100nm-330nm, such as 100nm-200nm, 200nm-330nm, 300nm-400nm. When the nanoscale carbon graphitization catalyst within the above particle size range is mixed with other materials, a higher contact area with the carbon source can be obtained as much as possible, thereby improving the catalytic efficiency. The above average particle size is calculated based on the longest diameter of the primary particles.

[0060] In some embodiments, in order to maximize the conversion rate of graphene and better improve the conductivity of the polyanionic cathode material, in some embodiments, the mass ratio of the carbon graphitization catalyst to the carbon source is 1:100-1:30, such as 1:100, 5:312, 10:312, and can be optionally 1:63-1:30.

[0061] In some embodiments, the mixed slurry further comprises a lithium doping element raw material, a phosphorus doping element raw material, an iron doping element raw material, and an oxygen doping element raw material. The amount or proportion of the lithium source, phosphorus source, iron source, lithium doping element raw material, iron doping element raw material, phosphorus doping element raw material, phosphorus doping element raw material, and oxygen doping element raw material in the present application can be based on the amount or proportion used in the synthesis of conventional phosphate-based positive electrode materials, or based on the composition of the phosphate-based positive electrode material to be prepared. Usually, in order to improve the performance such as cycle performance, specific capacity or rate, relatively more iron source and iron doping element raw material are selected. In some embodiments, in the mixed slurry, the total molar number of lithium element in the lithium source and the doping element in the lithium doping element raw material is M1, the total molar number of iron element in the iron source and the doping element in the iron doping element raw material is M2, the total molar number of phosphorus element in the phosphorus source and the doping element in the phosphorus doping element raw material is M3, M1:M2:M3 is (1.0-1.1): (0.95-1.0) (1.0-1.1), and M2:M3 is less than 1:1. When a metal oxide is used as a carbon graphitization catalyst, the metal oxide can not only be used as a catalyst, but also the metal element therein can be used as an additional doping element to enter the skeleton structure of the phosphate-based positive electrode material during sintering, so the amount of iron element in the iron source and the doping element in the iron doping element raw material can be appropriately reduced. In the above molar ratio, M2 is less than M3, and the smaller M2 is, the larger the particle size of the composite positive electrode material obtained under the same calcination conditions, and the greater the compaction density.

[0062] Of course, if the mixed slurry does not include the corresponding lithium doping element raw materials, phosphorus doping element raw materials, iron doping element raw materials, and oxygen doping element raw materials, the above M1, M2 and M3 also do not include the molar number of the corresponding doping element.

[0063] However, if M2:M3 is too small, the gram capacity of the composite positive electrode material will be reduced. In some embodiments, M2:M3 is greater than or equal to 0.96:1 and less than 1:1, so that the compaction density and gram capacity can be improved as much as possible.

[0064] When the carbon graphitization catalyst selects metal oxide, although it can be used as a doping element, its main function is still to catalyze the conversion of carbon into graphene. In some embodiments, the ratio of the mass of the carbon graphitization catalyst to the total mass of the iron source and the iron-doping element raw material is (1:1000)-(1:100), preferably (1:300)-(1:100), so that the role of the catalyst, the iron source and the iron-doping element is fully exerted, and it will not cause excessive residue of the carbon graphitization catalyst. In addition, the amount of the graphitization catalyst used within the above-mentioned ratio range also makes the graphene content produced at an appropriate level, avoiding the negative effects that are easily caused by too high a graphene content, such as excessive viscosity of the positive electrode slurry and difficulty in construction.

[0065] The phosphorus source, iron source, optional lithium-site doping element raw material, optional iron-site doping element raw material, phosphorus-site doping element raw material, optional phosphorus-site doping element raw material, and optional oxygen-site doping element raw material used in the present application can be selected from sulfates, nitrates, carbonates, hydrochlorides, phosphates, oxalates and other salt substances of each element.

[0066] In some embodiments, the polyanionic cathode material includes a lithium-containing phosphate, and the lithium-containing phosphate includes at least one of lithium iron phosphate and a doped and / or coated modified compound thereof. In some embodiments, the prepared lithium-containing phosphate includes a molecular formula of Li m A a Fe x D d P y E e O z G gA includes at least one element selected from Al, Na, K or Mg; D includes at least one element selected from Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, Ti or V; E includes at least one element selected from B, S, Si or N; G includes at least one element selected from S, F, Cl or Br; m is selected from the range of 0.5 to 1.15 (e.g., 0.5, 0.6, 0.7, 0.8, 0.9, 1.0 or 1.1); a is selected from the range of 0 to 0.1 (e.g., 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.1) ; x is selected from the range of 0.5 to 1 (such as 0.5, 0.6, 0.7, 0.8, 0.9 or 1); d is selected from the range of 0 to 0.5 (such as 0, 0.1, 0.2, 0.3, 0.4 or 0.5); y is selected from the range of 0.5 to 1 (such as 0.5, 0.6, 0.7, 0.8, 0.9 or 1); e is selected from the range of 0 to 0.5 (such as 0, 0.1, 0.2, 0.3, 0.4 or 0.5); z is selected from the range of 3.5 to 4 (such as 3.5, 3.6, 3.7, 3.8, 3.9 or 4.0); g is selected from the range of 0 to 0.5 (such as 0, 0.1, 0.2, 0.3, 0.4 or 0.5). For example, the above-mentioned element A is a lithium doping element, the element D is an iron doping element, the element E is a phosphorus doping element, and the element G is an oxygen doping element. The carbon material described in the above embodiments is coated on the surface of the above lithium-containing phosphate and / or dispersed between the particles of the lithium-containing phosphate.

[0067] In some embodiments, the iron source includes at least one of ferric phosphate and ferrous oxalate; the lithium source includes at least one of lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium nitrate, lithium carbonate, lithium phosphate, lithium hydroxide or lithium acetate; the phosphorus source includes at least one of diammonium dihydrogen phosphate, ammonium phosphate, lithium phosphate, phosphoric acid, and iron phosphate.

[0068] The amount of solvent in the mixed slurry affects the grinding and mixing effect and the drying efficiency. When the solvent is more, it is beneficial to improve the uniformity of the material; when the solvent is less, it is beneficial to improve the drying efficiency. The above-mentioned solvent can be selected from commonly used volatile solvents, such as water, ethanol, etc. In some embodiments, the solvent is water. In some embodiments, the total mass of the lithium source, phosphorus source, iron source, optional lithium-doping element raw material, optional iron-doping element raw material, phosphorus-doping element raw material, optional phosphorus-doping element raw material, phosphorus-doping element raw material, and optional oxygen-doping element raw material to the mass ratio of the solvent is (1-3): (1-7).

[0069] The above grinding can refine the insoluble particles in the mixed slurry on the one hand, and promote the mixing of insolubles on the other hand. In some embodiments, the above grinding includes ball milling and sand milling performed sequentially; the Dv50 of the insoluble particles in the mixed slurry after ball milling is 2.0μm-5.0μm, which can be optionally 2.0μm-4.0μm; the Dv50 of the insoluble particles in the mixed slurry after sand milling is 0.3μm-1.2μm, which can be optionally 0.3μm-0.4μm. The particle size of the insoluble particles is adjusted by controlling the time and speed of ball milling and sand milling. In some embodiments, the ball milling temperature is adjusted to 25℃-35℃, the ball milling speed is 800rpm-2000rpm, and the ball milling time is 0.5h-4h to obtain insoluble particles in the above Dv50 range. In some embodiments, the sand milling temperature is adjusted to 25° C.-35° C., the sand milling speed is 5000 rpm-10000 rpm, and the sand milling time is 0.5 h-4 h to obtain insoluble particles within the above Dv50 range.

[0070] The above Dv50 is tested using a laser particle size analyzer (Malvern 3000).

[0071] In some embodiments, the drying in the above preparation method can adopt a drying method commonly used in the art, such as spray drying, heating drying, etc. In some embodiments, the drying is selected to be spray drying. The inlet air temperature and outlet air temperature of spray drying affect the drying state of the mixed dry matter, such as the size and water content of the particles. In some embodiments, the inlet air temperature is controlled to be 200°C to 300°C and the outlet air temperature is controlled to be 90°C to 120°C during the spray drying process. Under the above conditions, spray drying can obtain a good uniformity of the mixed dry matter particles, and the water content can be controlled to be below 2%.

[0072] The process of sintering the mixed dry matter can be based on the conventional sintering process. In some embodiments, the process of sintering the mixed dry matter includes: heating the mixed dry matter to 780°C-820°C for 2h-9h, and keeping the temperature at 780°C-820°C for 6h-20h, such as heating to 780°C, 790°C, 800°C, 810°C or 820°C. By controlling the above sintering conditions, the powder compaction density and graphene content of the obtained composite positive electrode material are further balanced, so that the discharge gram capacity and energy density of the battery are optimized as much as possible.

[0073] In some embodiments, sintering is performed in a reducing atmosphere, and the reducing atmosphere includes any one or more of hydrogen, acetone, propylene, carbon monoxide, methanol, acetylene, methane, ethylene, and ethane. In some embodiments, the reducing atmosphere also includes a protective gas, and the protective gas is nitrogen and / or an inert gas.

[0074] The addition of a reducing atmosphere is not only beneficial to increasing the carbonization rate of the carbon source, but also has a significant improvement effect on the catalytic effect of the carbon graphitization catalyst in the form of metal oxides, further optimizing the carbon graphitization effect, so that the composite positive electrode material contains more graphene content.

[0075] In some embodiments, the volume content of the reducing gas in the reducing atmosphere is 1%-8%. It should be noted that the volume content is calculated based on the volume of the reducing gas and the protective gas. When the reducing gas content is within the above range, it can not only improve the carbonization rate, but also facilitate the conversion rate of the metal elements of each metal element-containing raw material in the preparation of the positive electrode material to the positive electrode material.

[0076] The composite positive electrode material obtained after sintering is agglomerated. In order to facilitate the subsequent preparation of positive electrode sheets, in some embodiments, after sintering, the preparation method also includes a process of crushing the composite positive electrode material. In order to further improve the compaction density of the composite positive electrode material, in some embodiments, the Dv50 of the crushed composite positive electrode material is adjusted to 0.6μm-2.0μm.

[0077] The second embodiment of the present application provides a composite positive electrode material, which includes a polyanionic positive electrode material and a carbon material, wherein the carbon material is coated on at least a portion of the surface of the polyanionic positive electrode material and / or dispersed between the polyanionic positive electrode material particles, the carbon material includes graphene, and the powder compaction density of the composite positive electrode material at 226.0738Mpa is ≥2.42g / cm 3 , optionally ≥2.53g / cm 3 .

[0078] The composite positive electrode material can be prepared by the above-mentioned preparation method of the present application. The composite positive electrode material contains graphene, which can improve the conductivity of the composite positive electrode material. And the composite positive electrode material has a higher compactness, so the battery has a higher energy density.

[0079] The content of graphene not only affects the conductivity of the composite positive electrode material, but also affects the compaction density of the composite positive electrode material and the turbidity of the positive electrode slurry. When the content of graphene increases, on the one hand, due to the increase in the conductivity of graphene, the discharge capacity of the battery cell can be improved. On the other hand, due to the layered characteristics of graphene, the surface lubricity of the composite positive electrode material will be further improved, which is conducive to the close contact between particles, thereby increasing the compaction density; since the adhesion of graphene between particles increases with the increase of graphene content, the turbidity of the positive electrode slurry containing the composite positive electrode material increases. If the content of graphene in the composite positive electrode material is too high, it will cause the turbidity of the composite positive electrode material to be too high, which will make it difficult to coat the positive electrode slurry, affecting the construction efficiency and the morphology of the positive electrode film layer; and if the content of graphene in the composite positive electrode material is too high, it will also cause the effective proportion of active materials to decrease, thereby reducing the compaction of the electrode sheet and the discharge capacity. In some embodiments, the graphene content is measured by the turbidity of the slurry formed by mixing the composite positive electrode material and water in a mass ratio of 1:40. In order to improve the three properties of conductivity, compaction density and coating of the positive electrode slurry as much as possible, the room temperature turbidity of the slurry formed by mixing the composite positive electrode material and water in a mass ratio of 1:40 is 200FTU-400FTU, and can be 240FTU-280FTU. The room temperature of the present application is 15°C-35°C as commonly understood in the art.

[0080] The above turbidity was measured using a HACH 2100Q turbidity meter according to the instructions.

[0081] In some embodiments, the mass content of the magnetic substance in the composite positive electrode material is ≤1 ppm, thereby controlling the self-discharge of the composite positive electrode material and extending the life of the battery having the composite positive electrode material.

[0082] [Positive electrode]

[0083] A positive electrode sheet includes a positive electrode film layer, the positive electrode film layer includes a positive electrode active material, and the positive electrode active material includes any one of the composite positive electrode materials provided in the second embodiment.

[0084] Since the composite positive electrode material of the present application contains graphene, the conductivity and compaction density of the composite positive electrode material are improved, so the compaction density and coulombic efficiency of the positive electrode sheet having the composite positive electrode material are also better.

[0085] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0086] In some embodiments of the present application, based on the total cross-sectional area of ​​the positive electrode active material, the cross-sectional area of ​​the composite positive electrode material with a primary average particle size of 50nm-150nm accounts for 10% to 35%; the cross-sectional area of ​​the composite positive electrode material with a primary average particle size of 150nm-1500nm accounts for 30% to 60%; the cross-sectional area of ​​the composite positive electrode material with a primary average particle size of not less than 1500nm accounts for 10-35%. The composite positive electrode material in the positive electrode sheet has small particle size particles, medium particle size particles and large particle size particles, and the particle size between particles is graded, which can further improve the compaction density of the positive electrode sheet. The above-mentioned composite positive electrode materials of different particle sizes can be adjusted by using the different particle sizes of the raw material particles during preparation, or the composite positive electrode materials with different particle size ranges can be mixed to obtain.

[0087] The above cross-sectional area ratio is tested by the following method: the positive electrode sheet is cut perpendicularly to the positive electrode sheet using an argon ion beam to expose the cross section, the cross section is photographed using a scanning electron microscope, and the longest diameter of the lithium iron phosphate salt particles is statistically analyzed using the long diameter statistical method. Among them, the "primary average particle size" refers to the average value of the primary particle size of all particles, which is numerically equal to the total particle size value divided by the total number of particles. Among them, the primary particle size in the cross-sectional diagram refers to the longest distance connecting two points through the edge.

[0088] Since particles with a primary average particle size of ≤50nm are prone to adhesion, there are large errors in statistics and it is difficult to clearly identify them individually. Therefore, during the particle size statistics process, particles with a primary average particle size of ≤50nm are not included in the statistical range.

[0089] The quantity content of the composite positive electrode material with a primary average particle size of 50nm-150nm is calculated by dividing the quantity of the composite positive electrode material with a primary average particle size of 50nm-150nm in the section by the total quantity of the positive electrode material.

[0090] The quantity content of the composite positive electrode material with a primary average particle size of 150nm-1500nm is calculated by dividing the quantity of the composite positive electrode material with a primary average particle size of 150nm-1500nm in the section by the total quantity of the positive electrode material.

[0091] The cross-sectional area percentage of the composite positive electrode material with a primary average particle size of not less than 1500 nm is calculated by dividing the cross-sectional area of ​​the composite positive electrode material with a primary average particle size of not less than 1500 nm in the cross section by the total area of ​​the positive electrode material.

[0092] The area of ​​the active material was obtained by statistically analyzing the scanning electron microscopy images of the positive electrode cross-section obtained using Avizo 3D software.

[0093] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0094] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0095] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0096] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0097] [Negative electrode]

[0098] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0099] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0100] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0101] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0102] In some embodiments, the negative electrode film layer may further include a binder. As an example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0103] In some embodiments, the negative electrode film layer may further include a conductive agent. As an example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0104] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0105] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0106] [Electrolytes]

[0107] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0108] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.

[0109] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0110] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0111] In some embodiments, the electrolyte may further include additives. As examples, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0112] [Isolation film]

[0113] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0114] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0115] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0116] In some embodiments, the secondary battery includes a secondary battery cell, or includes a battery module and a battery pack.

[0117] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0118] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0119] The present application has no particular limitation on the shape of the secondary battery cell, which may be cylindrical, square or any other shape. Figure 3 The secondary battery cell 5 is a square structure as an example.

[0120] In some embodiments, reference Figure 4 , the outer packaging may include a shell 51 and a top cover assembly 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0121] In some embodiments, secondary battery cells may be assembled into a battery module. The number of secondary battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0122] Figure 5 4 is an example of a battery module. Figure 5 In the battery module 4, the plurality of secondary battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary battery cells 5 may be fixed by fasteners.

[0123] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary battery cells 5 are received in the receiving space.

[0124] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0125] Figure 6 and Figure 7 1 is a battery pack 1 as an example. Figure 6 and Figure 7 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0126] In addition, the present application also provides an electric device, which includes a secondary battery provided in the present application. The secondary battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0127] As the electrical device, a secondary battery cell, a battery module or a battery pack may be selected according to its usage requirements.

[0128] Figure 8 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0129] [Example]

[0130] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0131] Preparation Example 1

[0132] A mixed carbon source formed by lithium carbonate, iron phosphate, diammonium phosphate, glucose and polyethylene glycol in a mass ratio of 90:35, a carbon graphitization catalyst Fe2O3 and water are mixed to form a mixed slurry, wherein the molar ratio of lithium element in lithium carbonate, iron element in iron phosphate, and phosphorus element in iron phosphate and diammonium phosphate is 1.01:1:1.03, the mass ratio of the total mass of lithium carbonate, iron phosphate and diammonium phosphate to water is 2:3, the mass of Fe2O3 is 0.5% of the mass of iron phosphate, the average particle size of Fe2O3 is in the range of 200nm-330nm, and the mass ratio of Fe2O3 to the mixed carbon source is 5:312.

[0133] The mixed slurry is sequentially ball-milled, sand-milled and spray-dried to obtain a mixed dry matter, wherein the ball-milling temperature is 25-35°C, the ball-milling time is 2h, and the ball-milling speed is 1000rpm; the Dv50 of the particles of the insoluble matter in the mixed slurry after ball-milling is 4μm; the sand-milling temperature is 25-35°C, the sand-milling time is 2h, the sand-milling speed is 8000rpm, and the Dv50 of the particles of the insoluble matter in the mixed slurry after sand-milling is 0.4μm; and the inlet air temperature during spray-drying is 250°C and the outlet air temperature is 100°C.

[0134] The mixed dry matter is sintered and crushed to obtain a composite lithium iron phosphate positive electrode material, wherein the sintering atmosphere includes nitrogen and acetylene, and the volume ratio of acetylene to nitrogen is controlled to be 2:98 by the amount of nitrogen and acetylene introduced during the sintering process, and the sintering process is heated to 780°C and then kept warm, the heating time is t1, and the keeping time is t2; t1 is 6 hours, t2 is 13 hours, and the obtained composite lithium iron phosphate positive electrode material includes lithium iron phosphate and a carbon coating coated on at least a portion of the surface of the lithium iron phosphate, by Figure 1 The TEM image of the composite lithium iron phosphate cathode material (equipment model: Thermo Scientific-TalosF200SG2) shows that the carbon coating layer is adhered with graphene. The Dv50 of the composite lithium iron phosphate cathode material after crushing is 1.2μm.

[0135] Preparation Example 2

[0136] On the basis of Preparation Example 1, Fe2O3 with an average particle size in the range of 100nm-200nm is used to replace the Fe2O3 in Preparation Example 1, and the rest is the same as Preparation Example 1, to obtain the composite lithium iron phosphate positive electrode material of Preparation Example 2.

[0137] Preparation Example 3

[0138] On the basis of Preparation Example 1, Fe2O3 with an average particle size in the range of 300nm-400nm is used to replace the Fe2O3 in Preparation Example 1, and the rest is the same as Preparation Example 1, to obtain the composite lithium iron phosphate positive electrode material of Preparation Example 3.

[0139] Preparation Example 4

[0140] On the basis of Preparation Example 1, Fe2O3 with an average particle size of less than 100 nm was used to replace the Fe2O3 in Preparation Example 1, and the rest was the same as Preparation Example 1, to obtain the composite lithium iron phosphate positive electrode material of Preparation Example 4.

[0141] Preparation Example 5

[0142] On the basis of Preparation Example 1, Fe2O3 with an average particle size in the range of 420nm-550nm is used to replace the Fe2O3 in Preparation Example 1, and the rest is the same as Preparation Example 1, to obtain the composite lithium iron phosphate positive electrode material of Preparation Example 5.

[0143] Preparation Example 6

[0144] On the basis of Preparation Example 1, the amount of Fe2O3 was adjusted so that the mass ratio of Fe2O3 to the mixed carbon source was 1:100, and the mass ratio of Fe2O3 to iron phosphate was 0.312:100; the rest was the same as Preparation Example 1, and the composite lithium iron phosphate positive electrode material of Preparation Example 6 was obtained.

[0145] Preparation Example 7

[0146] On the basis of Preparation Example 1, the amount of Fe2O3 was adjusted so that the mass ratio of Fe2O3 to the mixed carbon source was 10:312, and the mass ratio of Fe2O3 to iron phosphate was 1:100; the rest was the same as Preparation Example 1, and the composite lithium iron phosphate positive electrode material of Preparation Example 7 was obtained.

[0147] Preparation Example 8

[0148] On the basis of Preparation Example 1, the amount of Fe2O3 was adjusted so that the mass ratio of Fe2O3 to the mixed carbon source was 1:312, and the mass ratio of Fe2O3 to iron phosphate was 1:1000; the rest was the same as Preparation Example 1, and the composite lithium iron phosphate positive electrode material of Preparation Example 8 was obtained.

[0149] Preparation Example 9

[0150] On the basis of Preparation Example 1, the amount of Fe2O3 was adjusted so that the mass ratio of Fe2O3 to the mixed carbon source was 0.5:312, and the mass ratio of Fe2O3 to iron phosphate was 1:2000; the rest was the same as Preparation Example 1, and the composite lithium iron phosphate positive electrode material of Preparation Example 9 was obtained.

[0151] Preparation Example 10

[0152] On the basis of Preparation Example 1, the amount of Fe2O3 was adjusted so that the mass ratio of Fe2O3 to the mixed carbon source was 20:312, and the mass ratio of Fe2O3 to iron phosphate was 1:50; the rest was the same as Preparation Example 1, and the composite lithium iron phosphate positive electrode material of Preparation Example 10 was obtained.

[0153] Preparation Example 11

[0154] On the basis of Preparation Example 1, the ball milling time and ball milling speed of the mixed slurry, and the time and speed of sand milling were adjusted to make the Dv50 of the insoluble particles in the mixed slurry after ball milling be 5μm, and the Dv50 of the insoluble particles in the mixed slurry after sand milling be 1.2μm. The rest was the same as in Preparation Example 1, and the composite lithium iron phosphate positive electrode material of Preparation Example 11 was obtained.

[0155] Preparation Example 12

[0156] On the basis of Preparation Example 1, the ball milling time and ball milling speed of the mixed slurry, and the time and speed of sand milling were adjusted so that the Dv50 of the insoluble particles in the mixed slurry after ball milling was 2 μm, and the Dv50 of the insoluble particles in the mixed slurry after sand milling was 0.3 μm. The rest was the same as in Preparation Example 1, and the composite lithium iron phosphate positive electrode material of Preparation Example 12 was obtained.

[0157] Preparation Example 13

[0158] On the basis of Preparation Example 1, carbon monoxide was used to replace acetylene during sintering, and the rest was the same as Preparation Example 1, to obtain the composite lithium iron phosphate positive electrode material of Preparation Example 13.

[0159] Preparation Example 14

[0160] On the basis of Preparation Example 1, the amount of acetylene and nitrogen introduced was adjusted during sintering so that the volume ratio of acetylene to nitrogen was 8:92, and the rest was the same as Preparation Example 1, to obtain the composite lithium iron phosphate positive electrode material of Preparation Example 14.

[0161] Preparation Example 15

[0162] On the basis of Preparation Example 1, acetylene was not used during sintering, and the rest was the same as Preparation Example 1, to obtain the composite lithium iron phosphate positive electrode material of Preparation Example 15.

[0163] Preparation Example 16 On the basis of Preparation Example 1, Fe3O4 was used to replace Fe2O3 as the carbon graphitization catalyst, and the rest was the same as Preparation Example 1 to obtain the composite lithium iron phosphate positive electrode material of Preparation Example 16.

[0164] Preparation Example 17

[0165] On the basis of Preparation Example 1, FeO was used to replace Fe2O3 as the carbon graphitization catalyst, and the rest was the same as Preparation Example 1 to obtain the composite lithium iron phosphate positive electrode material of Preparation Example 17.

[0166] Preparation Example 18

[0167] On the basis of Preparation Example 1, Fe powder was used to replace Fe2O3 as the carbon graphitization catalyst, and the rest was the same as Preparation Example 1 to obtain the composite lithium iron phosphate positive electrode material of Preparation Example 18.

[0168] Preparation Example 19

[0169] On the basis of Preparation Example 1, Ni powder was used to replace Fe2O3 as the carbon graphitization catalyst, and the rest was the same as Preparation Example 1 to obtain the composite lithium iron phosphate positive electrode material of Preparation Example 19.

[0170] Preparation Example 20

[0171] On the basis of Preparation Example 1, NiO was used to replace Fe2O3 as the carbon graphitization catalyst, and the rest was the same as Preparation Example 1 to obtain the composite lithium iron phosphate positive electrode material of Preparation Example 20.

[0172] Preparation Example 21

[0173] On the basis of Preparation Example 1, Mn3O4 was used to replace Fe2O3 as the carbon graphitization catalyst, and the rest was the same as Preparation Example 1 to obtain the composite lithium iron phosphate positive electrode material of Preparation Example 21.

[0174] Preparation Example 22

[0175] On the basis of Preparation Example 1, V2O5 was used to replace Fe2O3 as the carbon graphitization catalyst, and the rest was the same as Preparation Example 1 to obtain the composite lithium iron phosphate positive electrode material of Preparation Example 22.

[0176] Preparation Example 23

[0177] On the basis of Preparation Example 1, ferrocene was used to replace Fe2O3 as the carbon graphitization catalyst, and the rest was the same as Preparation Example 1 to obtain the composite lithium iron phosphate positive electrode material of Preparation Example 23.

[0178] Preparation Example 24

[0179] On the basis of Preparation Example 1, the amount of diammonium phosphate was reduced so that the molar ratio of lithium in lithium carbonate, iron in iron phosphate, and phosphorus in iron phosphate and diammonium phosphate was 1.01:1:1, and the rest was the same as Preparation Example 1 to obtain the composite lithium iron phosphate positive electrode material of Preparation Example 24.

[0180] Preparation Example 25

[0181] The sintering temperature of Preparation Example 1 was adjusted to 750°C, the heating time t1 was adjusted to 2h, the insulation time t2 was adjusted to 20h, and the rest was the same as Preparation Example 1.

[0182] Preparation Example 26

[0183] The sintering temperature of Preparation Example 1 was adjusted to 840°C, the heating time t1 was adjusted to 9 hours, the insulation time t2 was adjusted to 6 hours, and the rest was the same as Preparation Example 1.

[0184] Preparation Example 27

[0185] The sintering temperature of Preparation Example 1 was adjusted to 750°C, the heating time t1 was adjusted to 6 hours, the insulation time t2 was adjusted to 13 hours, and the rest was the same as Preparation Example 1.

[0186] Preparation Example 28

[0187] The sintering temperature of Preparation Example 1 was adjusted to 820°C, the heating time t1 was adjusted to 6 hours, the insulation time t2 was adjusted to 13 hours, and the rest was the same as Preparation Example 1.

[0188] Comparative Preparation Example 1

[0189] The difference from Preparation Example 1 is that Fe2O3 is not used as a catalyst. The TEM image of the obtained composite lithium iron phosphate positive electrode material is as follows: Figure 2 As shown, no graphene is observed.

[0190] Comparative Preparation Example 2

[0191] The sintering temperature of Preparation Example 1 was adjusted to 720°C, the heating time t1 was adjusted to 6 hours, the insulation time t2 was adjusted to 13 hours, and the rest was the same as Preparation Example 1.

[0192] Comparative Preparation Example 3

[0193] The sintering temperature of Preparation Example 1 was adjusted to 880°C, the heating time t1 was adjusted to 6 hours, the insulation time t2 was adjusted to 13 hours, and the rest was the same as Preparation Example 1.

[0194] The turbidity is tested using a HACH 2100Q turbidity meter. The test method is as follows:

[0195] Sample preparation: At room temperature, peel a 50mL centrifuge tube and weigh 1±0.01g of sample; weigh four parallel samples for each group of samples; peel an electronic balance and weigh 40g±0.1g of ultrapure water and powder; place the centrifuge tube on a longitudinal mixer and stir at 80r / min for 2h; Centrifugation: place the sample evenly in the centrifuge; set the centrifuge speed to "1500r / min" for 10min.

[0196] Calibration: Press the "Standard Curve" button in the lower left corner, use a lens cleaning cloth to clean the water stains and fingerprints on the surface of the standard solution bottle, then put in 0FTU (pure water), 20FTU, 100FTU and 800FTU standard solutions that have been shaken evenly and have no bubbles, and click the "Read" button to perform alignment calibration. After the calibration is completed, press the "Finish" button to save the result.

[0197] Test: At room temperature, take the centrifuge tube and the rubber cover out of the centrifuge steadily and place them on the table; hold the 3mL rubber-tipped dropper at the 1.5mL scale with your hand and insert it vertically into the middle of the centrifuge tube to absorb 2mL of solution at one time; place the sample bottle on an electronic balance to peel it, weigh 0.5±0.005g of solution and add 10±0.1g of ultrapure water; use a lens cleaning cloth to wipe off water stains and fingerprints on the surface of the sample bottle, then put it into the measuring port and cover it; click to confirm the test and record the data.

[0198] Method for determining the mass content of magnetic materials in composite lithium iron phosphate positive electrode materials:

[0199] 1) Weigh 1kg of sample, put it into a plastic bucket, add 6L of deionized water, use a plastic tube to cover a φ24mmx240mm magnetic bar (magnetic induction intensity is 6000GS), and then use a heat sealing clip to heat seal it. Put the magnetic bar into the plastic bucket and seal it together. Set the speed of the roller mixing bucket to 60 rpm and the stirring time to 15min. Put the sealed bucket on the equipment for stirring;

[0200] 2) Prepare another clean bucket, add 5±0.2L of deionized water into the bucket, flush the magnetic material on the plastic tube into the solvent, reseal the magnetic rod, and repeat the above steps twice to ensure the accuracy of the amount of magnetic material extracted;

[0201] 3) Prepare a clean 1L beaker, rinse all the magnetic substances on the plastic tube into the beaker, use a magnetic block to suck the bottom of the beaker, and rinse 2-3 times to remove the non-magnetic substances;

[0202] 4) Use a measuring cylinder to measure 10 mL of deionized water and add it to a 100 mL beaker. Then measure 10 mL of 36%-38% hydrochloric acid and slowly add it to the beaker. Pour the prepared hydrochloric acid solution into the beaker, seal it and place it in an ultrasonicator for 2 minutes;

[0203] 5) After the ultrasonic treatment is completed, take out the beaker and use a magnetic block at the bottom of the beaker to absorb and gather the magnetic material, and pour the acid solution in the beaker into the waste liquid bucket; rinse the magnetic material in the beaker 3 times, and inject an appropriate amount of deionized water for filtration.

[0204] 6) Use a filter membrane with a pore size of 0.45 microns. After filtration, place the filter paper with magnetic particles on the surface on the slide of the cleanliness microscope, put it in an oven, and dry it at 60°C for (10±2) minutes. After drying, weigh the filter membrane and calculate the content of magnetic substances. The higher the content of magnetic substances in the positive electrode material, the more serious the self-discharge phenomenon of the battery cell and the shorter the battery life.

[0205] Measurement of powder compaction density: a certain amount of powder is placed on a special compaction mold with a known diameter (for example, the special mold can be Sansi Zongheng UTM7305), with a metal sheet on the top and bottom of the mold, and the powder is placed in the middle. By applying a pressure of 226.0738Mpa (i.e. 3T) and testing the corresponding powder thickness at the same time, the compaction density is calculated using the formula ρ=m / v. The specific operation can refer to the standard: GB / T24533-2009.

[0206] Pole piece analysis: Use an argon ion beam to cut the positive electrode piece perpendicular to the positive electrode piece, expose the cross section, take a picture of the cross section using a scanning electron microscope, and use the long diameter statistical method to statistically analyze the longest diameter of the lithium iron phosphate salt particles. The area of ​​the active material is obtained by statistically analyzing the scanning electron microscope image of the positive electrode piece cross section obtained using Avizo 3D software. Record the cross-sectional area ratio A of the composite positive electrode material with a primary average particle size of 50nm-150nm; the cross-sectional area ratio B of the composite positive electrode material with a primary average particle size of 150nm-1500nm; the cross-sectional area ratio C of the composite positive electrode material with a primary average particle size of not less than 1500nm.

[0207] Gram Capacity Test:

[0208] The preparation and testing process of the battery is as follows: 2.0000g of the positive electrode active material, conductive carbon black and PVDF of the corresponding preparation example are mixed in a mass ratio of 0.9:0.05:0.05, and then an organic solvent NMP (N-methylpyrrolidone) is added. After being fully mixed, a film with a thickness of 140 microns is coated on aluminum foil, vacuum dried at 120°C for 2h, and a round piece with a diameter of 13mm is punched using a puncher. The round piece is pressed at 10Mpa using a tablet press, and the positive electrode is kept in a vacuum at 120°C for 12h, and the weight of the positive electrode piece is weighed. A button cell is assembled in an argon-protected glove box, with a metal lithium sheet as the negative electrode, an electrolyte of a mixed solvent of EC (ethylene carbonate) and DMC (1,2-dimethyl carbonate) in a volume ratio of 1:1, an electrolyte of LiPF6, and a diaphragm of Celgard2400 microporous polyethylene film. The assembled battery is tested for electrical performance on a blue electric tester. In the voltage range of 2.0V to 3.75V, the specific capacity is tested by charging / discharging at 0.1C constant current for two weeks, and then charging / discharging at 1C constant current for two weeks. There is a constant voltage process during the charging process, the constant voltage is 3.75V, and the constant voltage cut-off current is 50μA.

[0209] Count the first 0.1C charging capacity in grams C1 and the first 1C discharging capacity in grams C2.

[0210] The test results are recorded in Table 1.

[0211] Table 1

[0212] According to the comparison between each preparation example and comparative preparation example 1, it can be seen that when a graphitization catalyst is used in the process of preparing the composite lithium iron phosphate positive electrode material, the turbidity of the slurry is significantly increased, indicating that graphene is generated therein and the discharge gram capacity of the corresponding button battery is increased.

[0213] According to the comparison of preparation examples 1 to 5, it can be seen that the particle size of the graphitization catalyst used affects the turbidity of the slurry, that is, affects the content of graphene. When the particle size grows to 200nm, as the particle size of the graphitization catalyst increases, the turbidity of the slurry increases, indicating that the content of graphene in the obtained material increases, indicating that the catalytic efficiency of the graphitization catalyst increases; however, when the particle size of the graphitization catalyst continues to increase to 400nm, the turbidity of the slurry does not increase, indicating that its catalytic efficiency has not increased significantly; when the particle size of the graphitization catalyst continues to increase, the turbidity of the slurry decreases instead, indicating that the particle size is too large and affects the catalytic effect of the graphitization catalyst.

[0214] According to the comparison of Preparation Example 1 and Preparation Examples 6 to 10, it can be seen that as the amount of graphitization catalyst increases, the turbidity of the slurry increases, indicating that the graphene content in the obtained material increases; however, when the graphene content is too much, the actual proportion of lithium iron phosphate active material in the composite material decreases, resulting in electrode compaction and reduced capacity.

[0215] According to the comparison of Preparation Example 1 and Preparation Examples 16 to 23, it can be seen that the catalytic efficiency of various graphitization catalysts is different. Moreover, when Preparation Examples 18 and 19 use metal as the graphitization catalyst, the metal has obvious residue in the positive electrode material, which is manifested as the content of magnetic substances in Table 1. The presence of magnetic substances affects the self-discharge of the battery, thereby affecting the battery life. In addition, when Preparation Example 23 uses ferrocene as the graphitization catalyst, since ferrocene is easy to burn during the roasting process, the corresponding slurry has a smaller turbidity and a lower graphene content, that is, the amount of graphene generated is less.

[0216] According to the comparative examples of preparation examples 1, 27, 28 and comparative preparation examples 2 and 3, it can be seen that within the range of 750°C-820°C, the proportion of particles with medium particle size in the composite positive electrode material is relatively large, so that the powder compaction of the material is within a more suitable range, and the turbidity of the slurry is relatively large, that is, the graphene content is relatively high, so the discharge gram capacity of the battery is higher. The sintering temperature of comparative preparation example 2 is below 750°C. The lower the sintering temperature, the greater the proportion of small particle size of the composite positive electrode material, the smaller the powder compaction, and thus the energy density of the battery cell is reduced; the sintering temperature of the comparative preparation example is above 840°C. The higher the sintering temperature, the smaller the turbidity of the slurry of the composite positive electrode material, so that the amount of graphene generated is smaller, and thus the discharge gram capacity of the corresponding button battery is reduced.

[0217] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A method for preparing a composite positive electrode material, wherein: The preparation method comprises: Mixing a lithium source, a phosphorus source, an iron source, a carbon source, and a carbon graphitization catalyst with a solvent in a predetermined ratio to form a mixed slurry; Grinding and drying the mixed slurry to obtain a mixed dry matter; The mixed dry matter is sintered to obtain a composite positive electrode material, and the sintering temperature is 750°C-840°C.

2. The preparation method according to claim 1, wherein The carbon graphitization catalyst includes any one or more of metals or metal oxides, the metal includes Fe and / or Ni, and the metal oxide includes any one or more of FeO, Fe3O4, Fe2O3, CuO, NiO, MnO, Mn3O4, V2O5, V2O3 or VO4.

3. The preparation method according to claim 1 or 2, wherein The average particle size of the carbon graphitization catalyst is 100nm-400nm.

4. The preparation method according to any one of claims 1 to 3, wherein The mass ratio of the carbon graphitization catalyst to the carbon source is 1:100-1:

30.

5. The preparation method according to any one of claims 1 to 4, wherein The mixed slurry also includes lithium-doping element raw materials, phosphorus-doping element raw materials, iron-doping element raw materials and oxygen-doping element raw materials. In the mixed slurry, the total molar number of lithium element in the lithium source and the doping element in the lithium-doping element raw materials is M1, the total molar number of iron element in the iron source and the doping element in the iron-doping element raw materials is M2, the total molar number of phosphorus element in the phosphorus source and the doping element in the phosphorus-doping element raw materials is M3, M1:M2:M3 is (1.0-1.1):(0.95-1.0):(1.0-1.1), and M2:M3 is less than 1:1, and the ratio of the mass of the carbon graphitization catalyst to the total mass of the iron source and the iron-doping element raw materials is (1:1000)-(1:100).

6. The preparation method according to claim 5, wherein: The M2:M3 is greater than or equal to 0.96:1 and less than 1:

1.

7. The preparation method according to any one of claims 1 to 6, wherein The polyanion positive electrode material includes a lithium-containing phosphate, and the lithium-containing phosphate includes at least one of lithium iron phosphate and a doped and / or coated modified compound thereof.

8. The preparation method according to any one of claims 1 to 7, wherein The carbon source includes one or more of glucose, sucrose, fructose, citric acid, starch, polyvinyl alcohol, polyethylene glycol or polyaniline.

9. The preparation method according to any one of claims 1 to 8, wherein The grinding includes ball milling and sand milling performed in sequence; the Dv50 of the insoluble particles in the mixed slurry after the ball milling is 2.0 μm-5.0 μm; the Dv50 of the insoluble particles in the mixed slurry after the sand milling is 0.3 μm-1.2 μm.

10. The preparation method according to any one of claims 1 to 9, wherein The process of sintering the mixed dry matter comprises: The mixed dry matter is heated to 780° C.-820° C. for 2 h-9 h, and kept at 780° C.-820° C. for 6 h-20 h.

11. The preparation method according to any one of claims 1 to 10, wherein The sintering is performed in a reducing atmosphere, which includes a reducing gas and a protective gas.

12. The preparation method according to claim 11, wherein The reducing gas includes any one or more of hydrogen, acetone, propylene, carbon monoxide, methanol, acetylene, methane, ethylene, and ethane.

13. A composite positive electrode material, comprising a polyanionic positive electrode material and a carbon material, wherein the carbon material is coated on at least a portion of the surface of the polyanionic positive electrode material and / or dispersed between particles of the polyanionic positive electrode material, wherein the carbon material comprises graphene, and wherein the powder compaction density of the composite positive electrode material at 226.0738 MPa is ≥ 2.42 g / cm 3 .

14. The composite cathode material according to claim 13, wherein: The powder compaction density of the composite positive electrode material at 226.0738Mpa is ≥2.53g / cm 3 .

15. The composite cathode material according to claim 13 or 14, wherein: The room temperature turbidity of the slurry formed by mixing the composite positive electrode material and water in a mass ratio of 1:40 is 200FTU-400FTU, and / or the mass content of the magnetic substance in the composite positive electrode material is ≤1ppm.

16. A positive electrode sheet, comprising a positive electrode film layer, wherein the positive electrode film layer comprises a positive electrode active material, wherein: The positive electrode active material includes the composite positive electrode material according to any one of claims 13 to 15.

17. The positive electrode sheet according to claim 16, wherein: Based on the total cross-sectional area of ​​the positive electrode active material, the cross-sectional area of ​​the composite positive electrode material with a primary average particle size of 50nm-150nm accounts for 10% to 35%; the cross-sectional area of ​​the composite positive electrode material with a primary average particle size of 150nm-1500nm accounts for 30% to 60%; the cross-sectional area of ​​the composite positive electrode material with a primary average particle size of not less than 1500nm accounts for 10-35%.

18. A secondary battery, comprising a positive electrode plate, wherein: The positive electrode plate includes the positive electrode plate according to claim 16 or 17.

19. An electrical device comprising a secondary battery, wherein: The secondary battery includes the secondary battery according to claim 18.

Citation Information

Patent Citations

  • Preparation of multi-position doped lithium iron phosphate positive electrode material and application thereof

    CN101339994A

  • High-conductivity ferrous phosphate lithium cathode material for lithium ion battery and preparation method thereof

    CN102324519A

  • Preparation method for lithium ion battery anode piece, and anode piece prepared by the same

    CN102376942A

  • Preparation method of lithium ion secondary battery anode material

    CN103400988A

  • Graphene in-situ composite lithium iron phosphate positive-electrode material and preparation method thereof

    CN108417801A

Cited By

  • COMPOSITE POSITIVE ELECTRODE MATERIAL, PREPARATION METHOD THEREFOR, POSITIVE ELECTRODE SHEET, SECONDARY BATTERY, AND ELECTRIC DEVICE

    EP4604207A1